Preparation method of C-Re-Ru / BP composite material catalyst and application of C-Re-Ru / BP composite material catalyst in efficient electro-catalysis hydrogen evolution reaction
By regulating the proportion of Re and Ru elements and phosphorus doping by hydrothermal method, a new C-Re-Ru/BP composite catalyst was designed, which solved the problem of poor catalyst durability in electrocatalytic seawater decomposition hydrogen production technology, achieved efficient and stable hydrogen evolution reaction, reduced costs, and was suitable for industrial applications.
Patent Information
- Application Number
- CN202411763050.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
AI Technical Summary
In the existing electrocatalytic seawater decomposition and hydrogen production technology, the durability of the anode and cathode catalysts is poor, especially the corrosion problems caused by the abundant chloride ions in seawater, which limits the industrial application of the technology.
By regulating the proportion of Re and Ru elements and the phosphorus doping content by hydrothermal method, a new C-Re-Ru/BP composite catalyst was designed. Combined with the unique properties of black phosphorus, the catalyst preparation method was optimized to form an efficient and stable electrocatalyst.
Compared with commercial Pt/C and Ru/C catalysts, the new C-Re-Ru/BP catalysts show better hydrogen evolution activity and stability in alkaline and neutral electrolytes, reducing costs and being suitable for industrial applications.
Smart Images

Figure CN119657183A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano-functional material chemistry and electrocatalysis, and relates to a preparation method of a novel C-Re-Ru / BP composite material catalyst and application of the catalyst in a highly efficient electrocatalytic hydrogen evolution reaction. Background Art
[0002] With the increase in global energy demand and the aggravation of environmental pollution, hydrogen energy as a new type of energy has attracted more and more widespread attention. At present, green hydrogen production technology by electrocatalytic water decomposition is of great significance to the conversion and storage of renewable energy. Among them, direct electrolysis of seawater is a renewable, scalable and potentially economical method for producing green hydrogen. However, the main challenge facing large-scale seawater electrolysis is the poor durability of anode and cathode catalysts. The abundant chloride ions in seawater will accelerate the corrosion of the catalyst, leading to the deactivation of active sites and even causing serious corrosion of water electrolysis devices, posing a huge challenge to its industrialization. Therefore, in order to achieve the widespread application of electrocatalytic seawater decomposition hydrogen production technology, it is extremely challenging to design and develop high-performance and high-stability hydrogen production electrocatalysts.
[0003] At present, platinum (Pt)-based catalysts are the most commonly used catalysts in alkaline hydrogen evolution reaction (HER) due to their excellent electrocatalytic activity. However, their large-scale application is limited by slow kinetics, poor stability, high price and scarcity. In order to reduce costs and improve performance, exploring cheaper elements to achieve the unity of activity and stability is currently a major difficulty. Considering that rhenium (Re) and ruthenium (Ru) have similar intrinsic activity and better alkaline resistance as Pt, and are cheaper, they are considered to be promising catalysts to replace Pt in hydrogen evolution reaction. However, Re nanoparticles are limited by their high temperature preparation conditions, and Ru catalysts are prone to agglomeration under alkaline conditions, resulting in a reduction in active sites and low catalytic efficiency, and poor stability. Therefore, exploring low-temperature preparation conditions is crucial for Re-based hydrogen evolution electrocatalysis. At the same time, alloying Re with Ru is very likely to solve the problems faced by a single metal element, which can not only solve the poor stability but also improve its catalytic activity to form an efficient non-Pt hydrogen evolution catalyst. Studies have shown that alloys also have the advantages of corrosion resistance and strong stability. In order to further improve the performance of Re-Ru alloy catalysts, a strategy combining optimization of alloy component ratio, carrier selection and modification, preparation method improvement and additive addition can be adopted. In current research, black phosphorus (BP) is considered to be a promising catalyst in the electrocatalytic hydrogen evolution reaction due to its unique physicochemical properties and efficient catalytic performance, but the hydrogen evolution performance of BP itself is not excellent. Based on this, it is particularly important to optimize the combination of the three to achieve a win-win situation of high activity and high stability.
[0004] Therefore, the present invention aims to design a new C-Re-Ru / BP composite catalyst by regulating the ratio of Re and Ru elements and the content of phosphorus doping through a hydrothermal method, which provides new ideas and methods for the development of efficient and stable water electrolysis / seawater HER catalysts. Summary of the invention
[0005] The object of the present invention is to provide a novel C-Re-Ru / BP composite material catalyst preparation method and application as an electrochemical hydrogen evolution reaction catalyst. The catalyst can be used for alkaline / neutral hydrogen evolution reaction, has better activity and stability than commercial Pt / C and Ru / C catalysts, has relatively low cost, good stability, and is suitable for industrial application.
[0006] The first object of the present invention is to provide a method for preparing a C-Re-Ru / BP composite catalyst, comprising the following steps: (1) Preparation of C-Re-Ru catalyst: dispersing carbon black in a solvent to obtain a carbon solution, then adding an ammonium perrhenate solution and a ruthenium chloride solution to the carbon solution respectively, stirring under heating conditions to form a precursor mixed solution, subjecting the precursor mixed solution to a thermal reaction, and calcining to obtain a C-Re-Ru catalyst; (2) Preparation of C-Re-Ru / BP catalyst: Dissolve the C-Re-Ru catalyst in a solvent and disperse it evenly. Then add the black phosphorus solution and disperse it evenly by ultrasonic at room temperature. Then, dry the obtained precipitate product in an oven at 80-100°C for 5-12 h.
[0007] In the step (1), the mass concentration of the ammonium perrhenate solution is 0.01-1 M; the mass concentration of the ruthenium chloride solution is 0.01-1 M. The solvent includes ethanol and isopropanol.
[0008] In the step (1), the thermal reaction temperature is 150-200°C, the reaction time is 1-8 hours, and the thermal reaction is carried out in a closed hydrothermal reactor.
[0009] During the calcination process, the calcination is carried out at 200-400° C. for 1-4 h in a H2 / N2 mixed atmosphere, wherein the H2 content in the H2 / N2 mixed atmosphere is 10-30%.
[0010] The black phosphorus solution is a product obtained by dispersing blocky black phosphorus in a solvent into a black phosphorus suspension, ultrasonicating, centrifuging, and washing. Finally, the concentration of the black phosphorus solution is determined using ultraviolet absorption spectroscopy (determined based on the absorbance at 808 nm).
[0011] The ultrasonic condition is to perform ultrasonic treatment in an ultrasonic probe of 1000W-2000W.
[0012] In step (2), the mass concentration of the C-Re-Ru catalyst is 0.1-2 mg / mL; the concentration of black phosphorus is 0.1-1.0 mg / mL.
[0013] In S2, the C-Re-Ru catalyst is dissolved in a solvent, and after being evenly dispersed, a black phosphorus solution is added (the black phosphorus solution is also evenly dispersed in the solvent), and nafion is added at room temperature for ultrasonic dispersion. The solvent includes ethanol and isopropanol.
[0014] In some embodiments, take (10-200 μL) C Re-Ru The concentration of BP is 0.1-2 mg / mL and (5-100 μL) BP is 0.1-1.0 mg / mL. Ultrasonicate for 40-60 min at room temperature, then add 30-50 μL nafion solution and ultrasonicate for another 20-30 min.
[0015] The test method of the hydrogen evolution reaction performance of the C-Re-Ru / BP catalyst prepared above in alkaline / neutral electrolyte: data collection was performed using a CHI1140D electrochemical workstation, and a three-electrode electrolytic cell was used for testing. A carbon rod was used as a counter electrode, saturated calomel was used as a reference electrode, and carbon paper (1cm x 1cm) coated with the above catalyst slurry was used as a working electrode. The electrolytes were 1 M KOH and pure seawater (the seawater was from Dameisha, Shenzhen). An activation test was performed before the electrochemical test. The scanning potential range of the activation process was -0.8~-1.4 V vs RHE, the scanning rate was 100 mV / s, and the CV curve was scanned until it was stable. Activity test: linear scanning voltammetry curve, scanning rate 100mV / s, scanning potential range -0.8~-1.4 V vs RHE. Stability test: chronopotentiometry, set the current density to 20 mA / cm -2 , test time 30h~150h.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a novel C-Re-Ru / BP composite material catalyst. The core of the method is to adjust the contents of Re and Ru elements on carbon by a hydrothermal method to form a partial metal Re-Ru alloy, and then optimize the C-Re-Ru catalyst by adding an appropriate amount of black phosphorus solution at room temperature. The prepared C-Re-Ru / BP catalyst has better hydrogen evolution activity and stability than commercial 10 wt% Pt / C and 5 wt% Ru / C catalysts. Among them, the C-Re-Ru / BP catalyst with the best performance only needs a hydrogen evolution overpotential of 23.6 mV to reach 10 mA cm in an electrolyte of 1 M KOH. -2The current density is 2.6 times and 5.1 times higher than that of commercial 10 wt% Pt / C and 5 wt% Ru / C catalysts, respectively. When the electrolyte is seawater, the current density is 10 mA cm -2 The hydrogen evolution overpotential under current density is 172.4 mV, which is 1.3 times and 1.8 times higher than that of commercial 10 wt% Pt / C and 5 wt% Ru / C catalysts, respectively. At the same time, its stability is also more advantageous. On the other hand, compared with commercial Pt / C and Ru / C, it can further reduce costs, is suitable for industrial applications, and realizes full utilization of resources and energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art; obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 This is the transmission electron microscope TEM of the C-Re-Ru / BP catalyst in Example 4 of the present invention.
[0019] Figure 2 It is the XRD diagram of the C-Re-Ru / BP catalyst in Examples 3 and 4 of the present invention.
[0020] Figure 3 The data graphs are of hydrogen evolution performance of C-Re-Ru / BP catalyst, 10wt% Pt / C and 5wt% Ru / C in 1M KOH electrolyte in Examples 4-5 of the present invention. (wt% in the graphs is abbreviated as %).
[0021] Figure 4 The data diagram of hydrogen evolution performance of C-Re-Ru / BP catalyst, 10wt% Pt / C and 5wt% Ru / C in seawater electrolyte in Examples 4 and 5 of the present invention is shown in Figure 1 (wt% is abbreviated as %).
[0022] Figure 5 The stability diagram of hydrogen evolution reaction of C-Re-Ru / BP catalyst in Example 4 of the present invention and 10wt%Pt / C and 5wt%Ru / C in Example 5 in 1M KOH electrolyte. (wt% in the figure is abbreviated as %). DETAILED DESCRIPTION
[0023] In order to make the purpose, technical effect and technical solution of the embodiment of the present invention clearer, the technical solution in the embodiment of the present invention is clearly and completely described below in conjunction with the drawings in the embodiment of the present invention; it is obvious that the described embodiment is a part of the embodiment of the present invention. Based on the embodiment disclosed in the present invention, other embodiments obtained by ordinary technicians in this field without making creative work should all fall within the scope of protection of the present invention.
[0024] Example 1 The present invention provides a method for preparing a novel C-Re composite catalyst, comprising the following steps: (1) Preparation of 0.1 M ammonium perrhenate solution: Dissolve 26.82 mg of ammonium perrhenate in 1 mL of deionized water and perform ultrasonic treatment for 30 min to completely dissolve the ammonium perrhenate solution.
[0025] (2) Preparation of C-Re catalyst: 0.05 g of carbon black was dispersed in 10 mL of ethanol and ultrasonically stirred for 30 min to form a uniformly dispersed carbon black solution. Then, 0.5 mL of 0.1 M ammonium perrhenate solution was added to the above carbon solution and stirred at room temperature for 1 h. Then, the mixture was placed on a magnetic stirring high-temperature hot plate at 80 °C and heated for 12 h to form a precursor mixed solution. The mixed solution was transferred to a 50 mL polytetrafluoroethylene hydrothermal reactor and reacted in an oven at 150 °C for 8 h. The mixture was washed alternately with deionized water and anhydrous ethanol and centrifuged. The precipitated product was dried in an oven at 80 °C for 12 h and calcined in a tubular furnace at 200 °C for 2 h using a 10% H2 / N2 mixed gas to obtain a C-Re catalyst.
[0026] Example 2 The present invention provides a method for preparing a novel C-Ru composite material catalyst, comprising the following steps: (1) Preparation of 0.1 M anhydrous ruthenium chloride solution: Dissolve 20.72 mg of ammonium perrhenate in 1 mL of deionized water and perform ultrasonic treatment for 30 min to completely dissolve it to obtain a 0.1 M anhydrous ruthenium chloride solution. (2) Preparation of C-Ru catalyst: 0.05 g of carbon black was dispersed in 10 mL of ethanol and ultrasonically stirred for 30 min to form a uniformly dispersed carbon solution. Then, 0.5 mL of 0.1 M anhydrous ruthenium chloride solution was added to the above carbon solution and stirred at room temperature for 1 h. Then, the mixture was placed on an 80 °C magnetic stirring high-temperature hot plate and stirred for 12 h to form a precursor mixed solution. The mixed solution was transferred to a 50 mL polytetrafluoroethylene hydrothermal reactor and reacted in a 150 °C oven for 8 h. The mixture was washed alternately with deionized water and anhydrous ethanol and centrifuged. The precipitated product was dried in an oven at 80 °C for 12 h and calcined in a tubular furnace at 200 °C for 2 h using a 10% H2 / N2 mixed gas to obtain a C-Ru catalyst.
[0027] Example 3 The present invention provides a method for preparing a novel C-Re-Ru composite material catalyst, comprising the following steps: (1) Preparation of 0.1 M ammonium perrhenate solution: Dissolve 241.45 mg of ammonium perrhenate in 9 mL of deionized water and perform ultrasonic treatment for 30 min to completely dissolve the ammonium perrhenate to obtain a 0.1 M ammonium perrhenate solution.
[0028] (2) Preparation of 0.1 M anhydrous ruthenium chloride solution: Dissolve 62.16 mg of ammonium perrhenate in 3 mL of deionized water and perform ultrasonic treatment for 30 min to completely dissolve it to obtain a 0.1 M anhydrous ruthenium chloride solution. (3) Preparation of C-Re-Ru catalyst: 0.05 g of carbon black was dispersed in 10 mL of ethanol and ultrasonically stirred for 30 min to form a uniformly dispersed carbon black solution. Then, 0.8 mL of 0.1 M ammonium perrhenate solution and 0.8 mL of 0.1 M anhydrous ruthenium chloride solution were added to the carbon black solution and stirred at room temperature for 1 h. The mixture was then placed on a 80 °C magnetic stirring high-temperature hot plate and stirred for 12 h to form a precursor mixed solution. The mixed solution was transferred to a 20 mL polytetrafluoroethylene hydrothermal reactor and reacted in an oven at 150 °C for 8 h. The mixture was washed alternately with deionized water and anhydrous ethanol and centrifuged. The precipitated product was dried in an oven at 80 °C for 12 h and calcined in a tubular furnace at 200 °C for 2 h using a 10% H2 / N2 mixed gas to obtain a C-Re-Ru catalyst.
[0029] (4) Preparation of catalyst slurry: 6.25 mg of C-Re-Ru catalyst was added to 2 mL of anhydrous ethanol and ultrasonicated for 30 min to make it uniformly dispersed to obtain C Re-Ru 0.5 mg / mL; take 40 μL C Re-Ru The 0.5 mg / mL solution was ultrasonicated for 20 min with 30 μL of Nafion solution.
[0030] XRD patterns of C-Re-Ru catalysts Figure 2 From the figure, it can be observed that after the Re-Ru combination, the characteristic diffraction peak of the catalyst has a slight shift, indicating that a Re-Ru alloy may be formed, which is beneficial to improving the performance of the catalyst.
[0031] Example 4 The present invention provides a method for preparing a novel C-Re-Ru / BP composite material catalyst, comprising the following steps: (1) Preparation of black phosphorus nanosheet solution: 100 mg of bulk black phosphorus was added to 50 mL of ethanol and ultrasonically stirred for 1 hour. The black phosphorus suspension was ultrasonically treated for 16 hours in an ice bath using a 1200 W ultrasonic probe. After stripping, the black phosphorus solution was centrifuged at 1000 rpm for 10 minutes to obtain the supernatant, which was then centrifuged at 12000 rpm for 15 minutes and washed three times with anhydrous ethanol. The precipitated product was added to 50 mL of anhydrous ethanol and ultrasonically dispersed for 30 minutes to obtain a black phosphorus nanosheet solution. 30 uL of the black phosphorus solution was diluted with 2970 uL of anhydrous ethanol and then the concentration was measured using ultraviolet absorption spectroscopy. The BP concentration was 3.49 mg / mL.
[0032] (2) Preparation of 0.1 M ammonium perrhenate solution: Dissolve 107.30 mg of ammonium perrhenate in 4 mL of deionized water and perform ultrasonic treatment for 30 min to completely dissolve the ammonium perrhenate to obtain a 0.1 M ammonium perrhenate solution.
[0033] (3) 0.1 M anhydrous ruthenium chloride solution: Dissolve 26.83 mg of ammonium perrhenate in 1 mL of deionized water and perform ultrasonic treatment for 30 min to completely dissolve it to obtain a 0.1 M anhydrous ruthenium chloride solution. (4) Preparation of C-Re-Ru catalyst: 0.05 g of carbon black was dispersed in 10 mL of ethanol and ultrasonically stirred for 30 min to form a uniformly dispersed carbon solution. Then, 2 mL of 0.1 M ammonium perrhenate solution and 0.5 mL of 0.1 M anhydrous ruthenium chloride solution were added to the carbon solution respectively and stirred at room temperature for 1 h. Then, the mixture was placed on a 80 °C magnetic stirring high-temperature hot plate and stirred for 12 h to form a precursor mixed solution. The mixed solution was transferred to a 50 mL polytetrafluoroethylene hydrothermal reactor and reacted in an oven at 150 °C for 8 h. The mixture was washed alternately with deionized water and anhydrous ethanol and centrifuged. The precipitated product was dried in an oven at 80 °C for 12 h and then calcined in a tubular furnace at 200 °C for 2 h using a 10% H2 / N2 mixed gas.
[0034] (5) Preparation of C-Re-Ru / BP catalyst: 20 mg of C-Re-Ru catalyst was dissolved in 4 mL of anhydrous ethanol and ultrasonicated for 30 min to make it uniformly dispersed to obtain C Re-Ru 500 μL of black phosphorus with a concentration of 3.49 mg / mL was added to the above metal solution, ultrasonicated at room temperature for 60 min, washed three times with anhydrous ethanol, centrifuged, and the precipitated product was dried in an oven at 80 °C for 12 h.
[0035] (6) Preparation of catalyst slurry: Add 6.25 mg of C-Re-Ru / BP catalyst into 2 mL of anhydrous ethanol and sonicate for 30 min to obtain a uniformly dispersed C-Re-Ru / BP solution. Take 100 μL of C-Re-Ru / BP solution and 30 μL of nafion solution and sonicate for 20 min.
[0036] Among them, C-Re-Ru / BP catalysts such as Figure 1 (a) TEM shows that Re and Ru are well dispersed and loaded on carbon. Figure 1 (b) shows that the size of the metal nanoparticles is less than 5 nm, and energy dispersive X-ray spectroscopy (EDS) confirms the doping of phosphorus. Figure 3 The hydrogen evolution reaction performance shows that in an electrolyte of 1 M KOH, only a 23.6 mV hydrogen evolution overpotential is required to reach 10 mA cm -2 The current density was increased by 2.6 times and 5.1 times compared with 10wt%Pt / C and 5wt%Ru / C catalysts, respectively. Figure 5 As shown, the C-Re-Ru / BP catalyst showed no obvious performance degradation under continuous stable testing for more than 80 hours in 1M KOH electrolyte.
[0037] Example 5 (1) The brand of 10 wt% Pt / C catalyst is Alfa Aesar, CAS: 7440-06-4; the brand of 5 wt% Ru / C catalyst is TGI, CAS: 7440-18-8.
[0038] (2) Preparation of 10 wt% Pt / C catalyst slurry: Weigh 5 mg of 10 wt% Pt / C catalyst and dissolve it in 1 mL of anhydrous ethanol. Ultrasonicate for 30 min to make it uniformly dispersed to obtain C Pt 0.5 mg / mL; 160 uL C Pt 0.5 mg / mL and 30uLnafion solution were ultrasonicated for 20 min to obtain 10wt% Pt / C.
[0039] (3) Preparation of 5wt%Ru / C catalyst slurry: 10 mg of 5wt%Ru / C catalyst was weighed and dissolved in 1 mL of anhydrous ethanol. Ultrasonication was performed for 30 min to uniformly disperse the catalyst to obtain C Ru 0.5 mg / mL; take 80 uL C Ru 0.5 mg / mL and 30uLnafion solution were ultrasonicated for 20 min to obtain 5wt%Ru / C.
[0040] The HER hydrogen evolution reaction performance of 10wt%Pt / C and 5wt%Ru / C catalysts is shown in Figure 2. Figure 3 and Figure 4 .
[0041] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.
Claims
1. A method for preparing a C-Re-Ru / BP composite catalyst, characterized in that: The steps include: (1) Preparation of C-Re-Ru catalyst: dispersing carbon black in a solvent to obtain a carbon solution, then adding an ammonium perrhenate solution and a ruthenium chloride solution to the carbon solution respectively, stirring under heating conditions to form a precursor mixed solution, subjecting the precursor mixed solution to a thermal reaction, and calcining to obtain a C-Re-Ru catalyst; (2) Preparation of C-Re-Ru / BP catalyst: Dissolve the C-Re-Ru catalyst in a solvent and disperse it evenly. Then add the black phosphorus solution and disperse it evenly by ultrasonic at room temperature. Then, dry the obtained precipitate product in an oven at 80-100°C for 5-12 h.
2. The method for preparing the C-Re-Ru / BP composite catalyst according to claim 1, characterized in that: In the step (1), the mass concentration of the ammonium perrhenate solution is 0.01-1M; the mass concentration of the ruthenium chloride solution is 0.01-1M.
3. The method for preparing the C-Re-Ru / BP composite catalyst according to claim 1, characterized in that: In the step (1), the thermal reaction temperature is 150-200°C, and the reaction time is 1-8 h.
4. The method for preparing the C-Re-Ru / BP composite catalyst according to claim 1, characterized in that: During the calcination process, the calcination is carried out at 200-400°C for 1-4 h in a H2 / N2 mixed atmosphere, wherein the H2 content in the H2 / N2 mixed atmosphere is 10-30%.
5. The method for preparing the C-Re-Ru / BP composite catalyst according to claim 1, characterized in that: The black phosphorus solution is a product obtained by dispersing blocky black phosphorus in a solvent into a black phosphorus suspension emulsion, and then ultrasonicating, centrifuging and washing.
6. The method for preparing the C-Re-Ru / BP composite catalyst according to claim 5, characterized in that: The ultrasonic condition is to perform ultrasonic treatment in an ultrasonic probe of 1000W-2000W.
7. The method for preparing a C-Re-Ru / BP composite catalyst according to claim 1, characterized in that: In step (2), the mass concentration of the C-Re-Ru catalyst is 0.1-2 mg / mL; the concentration of black phosphorus is 0.1-1.0 mg / mL.
8. A C-Re-Ru / BP composite catalyst, characterized in that: The C-Re-Ru / BP composite catalyst prepared by the method described in any one of claims 1 to 8 has a bimetallic alloy structure with a hexagonal close-packed structure; and characteristic absorption peaks are present at 25.8°, 38.1°, and 43.2° in the XRD characterization data.
9. An electrolytic hydrogen evolution material used under alkaline or neutral conditions, wherein the hydrogen evolution material is a C-Re-Ru / BP catalyst prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Three-dimensional carbon network loaded cobalt / black phosphorus quantum dot catalyst as well as preparation method and application thereof
CN116870949A
Active metal loaded carbon-based material, preparation method and application thereof, cathode electrode in total battery and preparation method of cathode electrode
CN117661010A
Ruthenium monatomic / nanoparticle high-efficiency hydrogen evolution catalyst as well as preparation method and application thereof
CN118621348A
Cited By
Synthesis process of Re-Ru-C catalyst for efficient alkaline electrolytic water hydrogen evolution
CN120330777A